The hidden curriculum of the Amazon future engineer educational program - Balán, Laura (Frontiers in Education, 2025)
This paper critically examines the Amazon Future Engineer (AFE) program, a global educational initiative designed to expand access to computer science education for underserved communities. While AFE promotes itself as a philanthropic intervention aimed at bridging the digital divide, this study interrogates its hidden curriculum and ideological foundations. Drawing on critical pedagogy, curriculum theory, educational sociology, and critical data studies, the paper argues that AFE serves as a vehicle for neoliberal ideology, prioritizing human capital development, corporate interests, and platform-based governance under the guise of technological inclusion. Through its emphasis on employability, standardized digital content, and scripted pedagogy, AFE reconfigures education as a site of economic productivity and brand expansion. The paper also critiques the program’s epistemic reductionism, its neglect of ethical, social, and ecological dimensions of engineering, and its disregard for more-than-human knowledge systems. By naturalizing technocratic values and depoliticizing educational goals, AFE contributes to the erosion of educational sovereignty and civic imagination. This analysis situates AFE within broader shifts in the political economy of education, marked by increasing corporate involvement and datafication. Ultimately, the paper calls for the development of alternative, justice-oriented pedagogical models that resist the colonization of education by market logics. By exposing the assumptions embedded in AFE’s design and discourse, the study invites educators, policymakers, and scholars to reimagine education as a democratic, relational, and decolonial practice grounded in ethical responsibility and collective agency.